Guid Fer A Laugh: A seriously fun look at Scottish comedy for those who take fun seriously (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
Guid Fer A Laugh has always sought to place itself as part of what Mikhail Bakhtin calls 'the open-ended dialogue that enters into the dialogic fabric of human life' (Morson & Emerson, 1990). It places a central value on the contributions of the participants and the active discourse that they create. As Buber (1965) states '[it is only] when we meet in the narrow ridge of the between' that we discover for ourselves new discourse, new knowledge and truth. This ‘meeting in dialogue’, especially applies to laughter.